Do the peak and mean force methods of assessing vertical jump force asymmetry agree? - Lake, J. P.; Mundy, P. D.; Comfort, P.; Suchomel, T. J. (Sports Biomechanics, 2020)
The aim of this study was to assess agreement between peak and mean force methods of quantifying force asymmetry during the countermovement jump (CMJ). Forty-five men performed four CMJ with each foot on one of two force plates recording at 1,000 Hz. Peak and mean were obtained from both sides during the braking and propulsion phases. The dominant side was obtained for the braking and propulsion phase as the side with the largest peak or mean force and agreement was assessed using percentage agreement and the kappa coefficient. Braking phase peak and mean force methods demonstrated a percentage agreement of 84% and a kappa value of 0.67 (95% confidence limits: 0.45-0.90), indicating substantial agreement. Propulsion phase peak and mean force methods demonstrated a percentage agreement of 87% and a kappa value of 0.72 (95% confidence limits: 0.51-0.93), indicating substantial agreement. While agreement was substantial, side-to-side differences were not reflected equally when peak and mean force methods of assessing CMJ asymmetry were used. These methods should not be used interchangeably, but rather a combined approach should be used where practitioners consider both peak and mean force to obtain the fullest picture of athlete asymmetry.